LITERATURE REVIEW : PENGARUH PENDIDIKAN KESEHATAN MENGGUNAKAN MEDIA AUDIOVISUAL TENTANG MENARCHE TERHADAP KESIAPAN SISWI SD MENGHADAPI MENARCHE - Tanti Suryawantie; K. Dewi Budiarti; Siti Rahmalia Nuraeni (Jurnal Keperawatan Dirgahayu (JKD), 2020)
Physical and mental readiness is needed before menarche because pre-puberty girl may feel anxiety and fear. Health education is one way that can be done because it will increase knowledge and information about menstruation so it will affect on good perceptions of menstruation and increase readiness in dealing with menarche. This research aimed to analyse the influence of health education by using audiovisual media on readiness to face menarche. This study uses the literature review method. The research was conducted by using Google Scholar and Proquest databases with keywords to find articles which are appropriate the inclusion and exclusion criteria to be reviewed. The results on reviewed articles, 3 articles prove that audiovisual education about menarche effective to increase readiness in dealing with menarche, 2 other articles prove that audiovisual media is more effective than the education without audiovisual media and leaflets. The conclusion based on 5 reviewed articles proves that audiovisual health education about menarche given to premenarche elementary student affect their readiness to face menarche because it can provide stimulus of sense for hearing and vision, so that the results obtained are more optimal. This review of the information on reproductive health can be used in the fields of education, approval, and community service regarding reproductive health in elementary school students.